Antipredator behaviour in semi-feral horses: innate response and the influence of external factors - Antoine Bercy; Francisco Ceacero; Martina Komárková (Animal Cognition)
Abstract Rewilding can play a vital role in safeguarding biodiversity, with the grazing pressure exerted by large ungulates and controlled by their predators being a significant factor, particularly in European contexts. Domestic horses are becoming integral to such ungulates’ biomass, but they may differ from truly wild species due to their domesticated origin. This raises concerns about whether feral horses retain adequate antipredator behaviours, especially in the presence of expanding, large predators like wolves. The field of antipredator behaviour research is hampered by inconsistent results and a lack of standardisation, and the behaviour of free-ranging horses remains underexplored. To address this gap, we conducted a playback experiment on semi-feral Exmoor ponies (n = 97) in the Czech Republic, exposing them to wolf howls, deer rut calls, and static noise as a control. We assessed alert behaviour and herd grouping while accounting for variables such as herd size, sex, time of day, weather conditions, environment type, presence of other ungulates, and habituation effects. Over 70% of the ponies exhibited alert behaviour in response to both wolf and deer calls. Although the magnitude of responses did not differ significantly between wolf and deer calls, both elicited distinct reactions compared to the control. Most of the studied external factors significantly affected the observed alert responses, highlighting that they must be carefully considered in such studies since these may explain the conflicting results observed in previous studies. The significant behavioural differences in reaction to the sounds indicate that the horses can differentiate them and likely still possess some innate memory, as reported in other ungulates. This is a positive sign towards reintroduction. Future research should carefully consider the validity of the testing environment, habituation effects, and other external factors to ensure robust results.